The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/srep14948
|View full text |Cite
|
Sign up to set email alerts
|

Exchanging ligand-binding specificity between a pair of mouse olfactory receptor paralogs reveals odorant recognition principles

Abstract: A multi-gene family of ~1000 G protein-coupled olfactory receptors (ORs) constitutes the molecular basis of mammalian olfaction. Due to the lack of structural data its remarkable capacity to detect and discriminate thousands of odorants remains poorly understood on the structural level of the receptor. Using site-directed mutagenesis we transferred ligand specificity between two functionally related ORs and thereby revealed amino acid residues of central importance for odorant recognition and discrimination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 47 publications
4
32
0
Order By: Relevance
“…One causative mechanism for differences in tuning breadth may be the size of the respective ligand-binding pockets. Baud et al suggested this for mouse receptors Olfr73 and Olfr74 [50]. Here, the ligand cavity size showed an accessible volume of 200 Å 3 for broadly tuned Olfr73, and 250 Å 3 for narrowly tuned Olfr74 [50].…”
Section: Introductionmentioning
confidence: 50%
“…One causative mechanism for differences in tuning breadth may be the size of the respective ligand-binding pockets. Baud et al suggested this for mouse receptors Olfr73 and Olfr74 [50]. Here, the ligand cavity size showed an accessible volume of 200 Å 3 for broadly tuned Olfr73, and 250 Å 3 for narrowly tuned Olfr74 [50].…”
Section: Introductionmentioning
confidence: 50%
“…Given that mice and rats are more closely related to pouched rats than to squirrels, we expected that orthologous genes might follow this pattern. We assume these genes should be orthologous and bind similar odorants with similar structures due to their similar protein sequences, however, it could be that small changes in these genes create ORs that bind different odorants, or change perception in other ways [20,21,71]. Identification of these potentially conserved ORs is important for understanding how the OR repertoire might respond to evolutionary pressures over time.…”
Section: Additions To Our Knowledge About Olfaction and Or Repertoirementioning
confidence: 99%
“…Which ORs bind which odorants is still largely unknown, as there are a number of technical limitations for high-throughput screening methods for ligand identification [14,15]. Despite these limitations, research shows that related ORs within subfamily groups (and orthologous OR genes among taxa) tend to bind structurally similar ligands [16], though the selectiveness and level of response by individual OSNs may vary [9,[17][18][19][20][21]. Although OSNs only contain one type of OR, the OR can bind a range of odorants causing this olfactory information to be coded using a combinatorial method [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian OSNs, both chemosensitivity and mechanosensitivity depends upon the Odorant Receptor (OR) they express . While odor‐dependent activation of these G protein‐coupled receptors (GPCRs) is, at least partly, understood , the molecular basis of their mechanosensitivity is less clear. One hypothesis is that mechanical stimuli deform OSN membranes to modulate the spontaneous (i.e.…”
Section: Polymodal Chemosensory and Mechanosensory Neurons And Receptorsmentioning
confidence: 99%